Kajian nilai kesemestaan dan kesetempatan rumah adat suku Batak Toba Rumah Bolon - Fauzi, Roikhan Amin (Maliki Interdisciplinary Journal, 2024)
Indonesia is a country rich in cultural diversity, one of which is reflected in the various traditional houses owned by each tribe. The bolon house, a traditional house of the Toba Batak tribe, is an example that illustrates the richness of this culture, reflecting local and universal values. Local values ​​can be seen from the use of local materials and architectural designs that are in harmony with the surrounding natural environment. Meanwhile, universal values ​​are manifested in universal principles such as harmony between humans, nature and ancestral spirits. This article discusses how the bolon house not only functions as a place to live, but also as a symbol of social status and tribal pride, which contains deep cultural meaning. To preserve and promote these values, efforts are needed through educational programs and cultural tourism, as well as the integration of knowledge about traditional houses in the educational curriculum. In this way, the local and universal values ​​of Rumah Bolon can continue to be preserved and introduced to the wider world.